2016
DOI: 10.1016/j.actbio.2015.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Cell penetrating peptide-modified poly(lactic-co-glycolic acid) nanoparticles with enhanced cell internalization

Abstract: The surface modification of nanoparticles (NPs) can enhance the intracellular delivery of drugs, proteins, and genetic agents. Here we studied the effect of different surface ligands, including cell penetrating peptides (CPPs), on the cell binding and internalization of poly(lactic-co-glycolic) (PLGA) NPs. Relative to unmodified NPs, we observed that surface-modified NPs greatly enhanced cell internalization. Using one CPP, MPG (unabbreviated notation), that achieved the highest degree of internalization at bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 94 publications
5
98
0
Order By: Relevance
“…18,21 Here, we produced spherical NPs with zeta potential values for unmodified (-25 mV) and BAR-modified NPs (-7 mV) that are consistent with other avidin-NPs studies. 19,20 Since unmodified NPs have a negative surface charge, this difference can be attributed to the successful conjugation of positively charged avidin and BAR peptide to the NPs surface. In addition to confirming successful conjugation, the more positive surface charge exhibited by avidin-NPs and BARmodified NPs may also facilitate electrostatic interactions of NPs with negatively charged moieties on the P. gingivalis cell surface.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…18,21 Here, we produced spherical NPs with zeta potential values for unmodified (-25 mV) and BAR-modified NPs (-7 mV) that are consistent with other avidin-NPs studies. 19,20 Since unmodified NPs have a negative surface charge, this difference can be attributed to the successful conjugation of positively charged avidin and BAR peptide to the NPs surface. In addition to confirming successful conjugation, the more positive surface charge exhibited by avidin-NPs and BARmodified NPs may also facilitate electrostatic interactions of NPs with negatively charged moieties on the P. gingivalis cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Briefly, 10 mg of avidin was dissolved in 1.2 mL of 2% (w/v) sodium deoxycholate (NaDC) in PBS and warmed to 37°C. A 1 mg/mL palmitic acid-Nhydroxysuccinimide ester (PA-NHS; Sigma-Aldrich, St Louis, MO, USA) solution was prepared in 2% (w/v) NaDC and sonicated until well-mixed.…”
Section: Synthesis Of Avidin-palmitatementioning
confidence: 99%
See 2 more Smart Citations
“…Steinbach et al found that decorating PLGA NPs with CPPs strikingly enhanced the cell binding and internalization of NPs. 34 Sánchez-Navarro et al reviewed various CPPs that facilitated biotherapeutics to transport across the intestinal barrier. 35 Last but not least, endosomal escape can also improve the effectiveness of drug delivery systems by protecting drug carriers from the acidified and degradative lysosome system.…”
mentioning
confidence: 99%